Cardiac Fibroblast-Specific Knockout of PGC-1α Accelerates AngII-Induced Cardiac Remodeling - Chen, Hong-jin; Pan, Xiao-xi; Ding, Li-li-qiang; Ruan, Cheng-chao; Gao, Ping-jin (Frontiers in Cardiovascular Medicine, 2021)
Cardiac remodeling is a pathological process of many heart diseases, consisted of ventricular hypertrophy and interstitial fibrosis. Fibroblasts are one of the major cells in myocardium, which regulate the balance of the generation and degeneration of collagen, and they convert into myofibroblasts in pathological state, contributing to the remodeling of heart. Peroxisome proliferator-activated receptor- γ (PPAR-γ) coactivator‐1α (PGC-1α) is vital to the function of mitochondria, which in heart can contribute to the energy production and reactive oxidative species (ROS) scavenging. In this study, we found that fibroblast-specific PGC-1α KO aggravated cardiac remodeling especially the fibrosis with or without the stimulation of Angiotensin II (AngII) in vivo and in vitro, accompanied with high level of oxidative stress response and inflammation.